Implementation of Rice Fish Farming as an Environmentally Friendly Alternative for Pest and Weed Control to Support Food Security in Talotenreng Village - Upe, Ambo; Adhan, Muhammad; Yanti , Novita Dwi; Putri, Harmin Adijaya; Rosadi, Sri Hardianti (BUMI: International Journal of Environmental Reviews, 2023)
One of the main problems faced by farmers is the decline in farming productivity, resulting in farmer incomes also not decreasing. Apart from that, the problem of pests and weeds is also a polemic for farmers who always rely on artificial chemicals to control them. As long as the farming system run by partner farmers is still monoculture, the farming results obtained only come from one commodity. Farmers have not yet aimed at diversifying their farming, so the income they earn is very dependent on the success of their monoculture farming. The solution offered to partners to the decline in production followed by the degradation of agricultural land whose quality is increasingly decreasing is to refer to the concept of organic farming, where the use of fertilizer production facilities is directed at the use of agricultural waste as a substitute for inorganic fertilizer, apart from being a fertilizer, also as food for fish that is environmentally friendly. Apart from that, the solution offered is the application of an integrated agricultural system with the "Mina Padi" model. This system will cultivate rice together with fish in one rice field area so that the level of pest and weed attacks on rice plantations can be minimized. Rice plants in rice fields will provide natural food for fish, while fish function as control of pests and weeds in rice plantations. Apart from that, fish is a source of nutrients for rice plants. The aim of this PKM activity is to provide alternative farming diversification for partner farmers in increasing farmer income, increasing farmer knowledge, and reducing the level of pest and weed attacks by creating natural enemies in an integrated farming concept designed in the mina padi system.